Work Engagement in the Public Service Context: The Dual Perceptions of Job Characteristics. Issue 13 (3rd October 2018) - Noesgaard, Mette Strange; Hansen, Jesper Rosenberg
ABSTRACT: Interest in work engagement research has increased significantly due to its positive influence on both employee and organizational performance. Studies show how engagement is explained through job characteristics in the Job Demands-Resource model, yet a more nuanced approach has been proposed. In this qualitative study, home caregivers' perceptions of job characteristics are investigated. Semi-structured interviews and observations reveal three main themes: Optimization, helping others, and emotional work. These show a dual perception of job characteristics consequently influencing the experienced engagement. Using Public Service Motivation literature, these dual perceptions are discussed.